MOTIVASI THAILAND MENJALIN KERJASAMA DENGAN INDONESIA DALAM BIDANG PERTAHANAN TAHUN 2015-2018 - Siti Hartisah; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to explain how defense cooperation is established between Thailand and Indonesia in 2015-2018. This collaboration is established because of threats that disturbed the stability of national security which were trans-national. To fulfill this matter then, Thailand is trying to strengthen its defense by cooperating with countries that have defense power like Indonesia. It is known that Indonesia is the strongest country in Southeast Asia, according to Global Fire Power source that presents the data that related to the strength and defense of countries in the world Thailand making Indonesia a partner in defense cooperation.The research data is obtained from books, journals, official documents, and websites that support the hypothesis, the researcher uses the neorealism approach of Kenneth Waltz and nation-state analysis. The theory used in this research is international cooperation from K.J. Holsti.The result of the research shows that the relationship between Thailand and Indonesia so far has been running well which can be seen from the implementation of the cooperation contained in the MoU and by holding work visits and honorary visits conducted by the two countries. The exchange of delegates or officers and joint training which is the scope of cooperation stated in the memorandum of understanding on increasing cooperation between Thailand-Indonesian defense officials and related defense activities was signed on May 21, 2015. keywords: Defense Cooperation, National Interest, Transnational Crime, Regional Sovereignty.